Entre Ruínas, Estilhaços E Silêncios: Uma Leitura Decrônica Da Casa Assassinada - Cruz Junior, Luiz Antonio Da [UNIFESP] (2018)
Crônica Da Casa Assassinada, A Novel Wrote By Lúcio Cardoso, In 1959, Occupies A Prominent Place Among The Main Works In The Brazilian Literature. In This Perspective, This Study Aims To Present An Analytical Reading Of The Novel. To Make This Possible, Considering The Narrative And Its Structure, This Research Intends To Point How The Plot Seems To Formalize A Representation That Is Not Limited To The Time Of The Narrative Or When It Was Written. So, First It Presents An Overview About The Criticism Reception About The Novel And About Its Author, Some Aspects Of His Life, And A Plot Summary. In Sequence, This Work Analyses The Narrative About Meneses Financial And Moral Ruin, The Allegories Two Characters (Timóteo Meneses And Nina), And A Probable Representative Formalization About The Society. Besides That, Within An Established Clipping, This Analysis Investigates André Meneses Journals To Observe The Textual Fragmentation That Occurs Throughout The Novel And Its Intrinsic Relation With The Subject That Pr